2019
DOI: 10.3390/su11226378
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Agricultural Practices in the Peripheral Areas of Côte d’Ivoire State-Owned Forests

Abstract: Côte d’Ivoire’s rural areas adjacent to the state-owned areas of the southern half of the country, such as classified forests, are experiencing significant migratory flows due to their agricultural potential. The population movements in these rural areas have changed the rural landscape. The general objective of this study was to identify the peasant innovations implemented in these rural areas adjacent to the state’s forest domains in a context of land saturation caused by migratory flows. This objective was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In addition, tree species retained by farmers in their cocoa farms were mainly composed of exotic and local fruit tree species, namely Persea americana, Mangifera indica and Citrus sp., confirming previous findings highlighting that fruit tree species were the major tree species in cocoa landscapes [18,29,35]. These species help cocoa farmers diversify their source of income and ensure their food security as fruits are either directly consumed or sold to local traders and farmers during the lean season [64,65]. Moreover, the association of fruit-tree species has the potential to enhance cocoa productivity, as shown in central Côte d'Ivoire through cocoa-avocado and cocoa-orange intercropping systems [18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, tree species retained by farmers in their cocoa farms were mainly composed of exotic and local fruit tree species, namely Persea americana, Mangifera indica and Citrus sp., confirming previous findings highlighting that fruit tree species were the major tree species in cocoa landscapes [18,29,35]. These species help cocoa farmers diversify their source of income and ensure their food security as fruits are either directly consumed or sold to local traders and farmers during the lean season [64,65]. Moreover, the association of fruit-tree species has the potential to enhance cocoa productivity, as shown in central Côte d'Ivoire through cocoa-avocado and cocoa-orange intercropping systems [18].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the origin of the farmer appears to be an underlying factor of agroforestry adoption. A recent appraisal conducted in Côte d'Ivoire related on-farm tree retention to the origin of farmers and are meant to supply their daily need for food, fuelwood, and traditional medicine [64]. Similarly, Owusu and Frimpong [31] showed that cocoa agroforestry adoption is triggered by several factors, including age, gender, and migration status, in Ghana and Cameroon [75].…”
Section: Discussionmentioning
confidence: 99%
“…Agroecological innovations we repeatedly encountered included growing nitrogen-fixing legumes for subsistence and improving soil fertility, and producing organic fertilisers from waste and chicken droppings. Many such innovations have been separately reported in the literature (Asare, 2006;Jagoret et al, 2014;Khatun et al, 2020;Zanh et al, 2019). In our study sites, we found that extension officers rarely consulted smallholders on their own sustainable innovations and environmental stewardship knowledge, despite both being expertly tailored to local conditions.…”
Section: Seeds Of a Liberation Environmentalitymentioning
confidence: 62%
“…Cote d'Ivoire is a coastal country in West Africa, covering 322,463 km 2 . Cote d'Ivoire is heavily dependent on agriculture and related activities [16].…”
Section: Investigation Sitesmentioning
confidence: 99%